Palladium(II)‐Catalyzed Enantioselective C−H Alkenylation of Ferrocenecarboxylic Acid. Issue 6 (11th February 2020) - Huang, Yanzhen; Pi, Chao; Cui, Xiuling; Wu, Yangjie
Abstract: The palladium‐catalyzed enantioselective C−H alkenylation of ferrocenecarboxylic acid has been developed. A series of 2‐alkenyl ferrocenecarboxylic acids with planar chirality were obtained using molecular oxygen as an oxidant. This protocol starts from less expensive and readily available starting materials and provides the target products as a key intermediate in organic synthesis. Abstract :